Policy-based hybrid hierarchical optical networks - Fawaz, W. (2017)
This document presents provisioning strategies for emerging hybrid optical networks. The idea is to make use of policy-based management that guides the behavior of a network through high-level declarative directives. In this regard and in the context of hybrid optical networks, policy rules are employed as the main means to extend the functionality of the control system and to complement its role in order to achieve the service provisioning